2000
DOI: 10.1007/s004670000303
|View full text |Cite
|
Sign up to set email alerts
|

Severe left ventricular hypertrophy in pediatric dialysis: prevalence and predictors

Abstract: Left ventricular hypertrophy (LVH) has been recognized as an independent risk factor for cardiovascular morbidity and mortality in adults with end-stage renal disease. However, the prevalence and severity of LVH in children on chronic dialysis therapy is not well established. Retrospectively, 64 chronic dialysis patients, aged 20 months to 22 years, on chronic dialysis had echocardiographic evaluation of LV mass (LVM) and geometry. Forty-eight (75%) children had LVH, including 22 of 26 (85%) on hemodialysis (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
136
3
8

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(155 citation statements)
references
References 27 publications
8
136
3
8
Order By: Relevance
“…The International Pediatric Peritoneal Dialysis Network (IPPN) is based on these same recommendations. Values previously estimated by Mitsnefes with a more limited number of patients, found that LVMI was 68-73% in patients in PD 7 and 80-85% in patients in HD 7,16 . The collaborative study published by the IPPN found that the use of height-associated LVMI provides the most prevailing prevalence of LVH in patients with PD 8 .…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The International Pediatric Peritoneal Dialysis Network (IPPN) is based on these same recommendations. Values previously estimated by Mitsnefes with a more limited number of patients, found that LVMI was 68-73% in patients in PD 7 and 80-85% in patients in HD 7,16 . The collaborative study published by the IPPN found that the use of height-associated LVMI provides the most prevailing prevalence of LVH in patients with PD 8 .…”
Section: Discussionmentioning
confidence: 70%
“…Mitsnefes M. et al (10) reported a figure of 75%, and the IPPN registry showed that only 26% of PD patients had normal heart condition 8 . The NA-PRTCS 2008 Registry showed that, from 4,000 patients on dialysis, 57% were with uncontrolled hypertension (> 95%), confirming that in patients with PD, hypertension and cardiac damage are most frequently associated with LVH 7 .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Approximately 75-85% of adult and pediatric patients on hemodialysis have left ventricular hypertrophy (LVH) on echocardiography (736,737). LVH is associated with increased mortality on hemodialysis (736) and peritoneal dialysis (738).…”
Section: Recommendationsmentioning
confidence: 99%
“…Potentially reversible risk factors for LVH in hemodialysis patients include anemia hypertension and IHD (Table 61) (737,743,744). An approach to IHD has been outlined above.…”
Section: Recommendationsmentioning
confidence: 99%